Organocatalyzed Atom Transfer Radical Polymerization: Perspectives on Catalyst Design and Performance - Theriot, Jordan C.; McCarthy, Blaine G.; Lim, Chern‐Hooi; Miyake, Garret M. (Macromolecular rapid communications., 2017)
The recent development of organocatalyzed atom transfer radical polymerization (O‐ATRP) represents a significant advancement in the field of controlled radical polymerizations. A number of classes of photoredox catalysts have been employed thus far in O‐ATRP. Analysis of the proposed mechanism gives insight into the relevant photophysical and chemical properties that determine catalyst performance. Discussion of each of the classes of O‐ATRP catalysts highlights their previous uses, their roles in the development of O‐ATRP, and the distinctive properties that govern their polymerization behavior, leading to a set of design principles for O‐ATRP catalysts. Remaining challenges for O‐ATRP are presented, as well as prospects for further improvement in the application scope of O‐ATRP. Organocatalyzed Atom Transfer Radical Polymerization (O‐ATRP) is a new variant of controlled radical polymerization. Here, different classes of photocatalysts for O‐ATRP are compared and contrasted in terms of the mechanism of O‐ATRP in order to highlight relevant design principles for catalysts. Remaining challenges and outlook for future advances in O‐ATRP are also discussed.